Microbiology and outcomes of community acquired pneumonia in non cystic-fibrosis bronchiectasis patients. Issue 1 (July 2015) - Polverino, Eva; Cilloniz, Catia; Menendez, Rosario; Gabarrus, Albert; Rosales-Mayor, Edmundo; Alcaraz, Victoria; Terraneo, Silvia; Puig de la Bella Casa, Jordi; Mensa, Josep; Ferrer, Miquel; Torres, Antoni
Summary Background It is general belief that Non-cystic fibrosis bronchiectasis (NCFB) is characterized by frequent community-acquired pneumonia. Nonetheless, the knowledge on clinical characteristics of CAP in NCFBE is poor and no specific recommendations are available. We aim to investigate clinical and microbiological characteristics of NCFBE patients with CAP. Methods Prospective observational study of 3495 CAP patients (2000–2011). Results We found 90 (2.0%) NCFBE-CAP that in comparison with non-bronchiectatic CAP (n, 3405) showed older age (mean ± [SD], NCFBE-CAP 73 ± 14 vs. CAP 65 ± 19yrs), more vaccinations (pneumococcal: 35% vs. 14%; influenza: 60% vs. 42%), comorbidities (n ≥ 2: 43% vs. 25%), previous antibiotics (38% vs. 22%), and inhaled steroids (53% vs. 16%) (p < 0.05 each). Streptococcus pneumoniae was the most frequent isolate in both groups (NCFBE-CAP 44.4% vs. CAP 42.7%; p = 0.821) followed by respiratory virus, mixed infections and atypical bacteria. Considering overall frequencies of the main pathogens (including monomicrobial and mixed infections) Pseudomonas aeruginosa (15.5% vs. 2.9%; p < 0.001) and Enterobacteriaceae (8.8% vs. 2.4%; p = 0.025) were more prevalent in NCFBE-CAP patients than in CAP. Despite these clinical and microbiological differences, NCFBE-CAP showed similar outcomes to CAP patients (mortality, length of hospital stay, etc.). Conclusions NCFBE-CAP patients are usually older and have more comorbidities but similar outcomes than general CAP population. Usual CAP pathogens, such as S. pneumoniae, are also involved in NCFBE-CAP but P. aeruginosa and other Enterobacteriaceae were globally more frequent than in CAP. Therefore, a wide microbiological investigation should be recommended in all NCFBE-CAP cases as well as routine pneumococcal vaccination for prevention of pneumonia.